Roles of a CCR4–NOT complex component GmNOT4-1 in regulating soybean nodulation - Zheng, Jiangtao; Sun, Lili; Wang, Dongmei; He, Lin; Du, Weijun; Guo, Shujin; Wang, Lixiang (Frontiers in Plant Science, 2023)
Legume-rhizobial symbiotic nitrogen fixation is the most efficient nitrogen assimilation system in the ecosystem. In the special interaction organ-root nodules, legume supply rhizobial carbohydrates for their proliferation while rhizobial provide host plant absorbable nitrogen. Nodule initiation and formation need a complex molecular dialogue between legume and rhizobia, which involves the accurate regulation of a series of legume genes. The CCR4-NOT complex is a conserved multi-subunit complex with functions regulating gene expression in many cellular processes. However, the functions of the CCR4-NOT complex in rhizobia-host interactions remain unclear. In this study, we identified seven members of the NOT4 family in soybean and further classified them into three subgroups. Bioinformatic analysis showed that NOT4s shared relatively conserved motifs and gene structures in each subgroup, while there were significant differences between NOT4s in the different subgroups. Expression profile analysis indicated that NOT4s may be involved in nodulation in soybean, as most of them were induced by Rhizobium infection and highly expressed in nodules. We further selected GmNOT4-1 to clarify the biological function of these genes in soybean nodulation. Interestingly, we found that either GmNOT4-1 overexpression or down-regulation of GmNOT4-1 by RNAi or CRISPR/Cas9 gene editing would suppress the number of nodules in soybean. Intriguingly, alterations in the expression of GmNOT4-1 repressed the expression of genes in the Nod factor signaling pathway. This research provides new insight into the function of the CCR4-NOT family in legume and reveals GmNOT4-1 to be a potent gene in regulating symbiotic nodulation.